SAT0511 CANAKINUMAB IN SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS: CLINICAL INACTIVE DISEASE RATE AND SAFETY IN ITALIAN PATIENTS. (June 2019) - Pardeo, Manuela; Bracaglia, Claudia; Piscitelli, Anna Lucia; Matteis, Arianna De; Tibaldi, Jessica; Alessio, Maria; Marino, Achille; Conti, Giovanni; Maggio, Maria Cristina; Alizzi, Clotilde; Licciardi, Francesco; Olivieri, Alma Nunzia; et al.
Abstract : Background: Systemic juvenile idiopathic arthritis (sJIA) is a polygenic autoinflammatory disease. The innate immune mechanisms play a central role with overproduction of inflammatory cytokines. The increased knowledge on the role of these cytokines has provided a change in the natural history of the disease with the introduction of the targeted treatments. Remarkable results has been observed with canakinumab, an anti-interleukin-1β monoclonal antibody, in two clinical trials but little information are available in real life. Objectives: To evaluate clinical inactive disease rate and safety of canakinumab in Italian patients with sJIA. Methods: We have collected retrospectively clinical and laboratory data of patients with sJIA treated with canakinumab in 9 Italian Pediatric Rheumatology centers. Clinically inactive disease (CID) at 6 months was defined according to Wallace criteria. We analyzed the effect of canakinumab on fever, rash, number of actives joints, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and physician's global assessment of disease activity score. Results: Forty seven patients (26 F) were included in the analyses. The median age (range) at the diagnosis and at the beginning of treatment with canakinumab was 7.6 (1-14.7) and 10.2 (1.7-22.2) years, respectively. Twenty seven patients (57.4%) had been previously treated with other biologic agents (18 with anakinra, 1 with tocilizumab, 6 with both and 2 with etanercept), withdrawn for inefficacy in 15/27 (55.5%). Thirty patients (63.8%) were receiving concomitant treatment with glucocorticoids at the median dose (range) of 0.69 (0.02-2.75) mg/kg/die. Thirtynine out of 47 patients had > 6 months of follow-up. Among these 39 patients, 27 (69.2%) achieved CID at 6 months and 5/27 (18.5%) were still on glucocorticoids. Of the 30 patients who received concomitant glucocorticoids at baseline, 24 achieved 6 months of follow-up and 12 (50%) of these were able to withdraw glucocorticoids. Minor adverse events were reported in 5/30 (16.6%) patients: upper respiratory tract infections in 4 and transient injection site reaction in 1. No cases of macrophage activation syndrome was reported. Conclusion: Our results provide initial real world evidence of the efficacy of treatment with canakinumab in patients with sJIA. In our study the percentage of patients who reached CID at 6 months is slightly higher (69.2%) than reported at the end (from 3 months to one year) of the 2 published randomized trials (60%). No serious adverse events were recorded in our population. Disclosure of Interests: Manuela Pardeo: None declared, Claudia Bracaglia: None declared, Anna Lucia Piscitelli: None declared, Arianna De Matteis: None declared, Jessica Tibaldi: None declared, Maria Alessio: None declared, Achille Marino: None declared, Giovanni Conti: None declared, Maria Cristina Maggio: None declared, Clotilde Alizzi: None declared, Francesco Licciardi: None declared, Alma Nunzia Olivieri: None declared, Giovanni Filocamo: None declared, Francesca Orlando: None declared, Silvana Martino: None declared, Rolando Cimaz: None declared, Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Fabrizio De Benedetti Grant/research support from: Abbvie, SOBI, Novimmune, Roche, Novartis, Sanofi, Pfizer